2019
DOI: 10.1055/s-0039-1694031
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum Group B Streptococcus Antibiotic Prophylaxis in Penicillin Allergic Pregnant Women

Abstract: Objectives To estimate the prevalence of and identify modifiable risk factors for alternative antibiotics for group B Streptococcus (GBS) prophylaxis in penicillin-allergic women. Methods Retrospective cohort study of pregnant women within a health care network from January 1, 2014, to December 31, 2017. Included women were GBS colonized, delivered at ≥ 37 weeks' gestation, and reported penicillin/cephalosporin allergy. The primary outcome was the use of alternate antibiotics GBS prophylaxis, defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
13
1
Order By: Relevance
“…Newborns exposed to IAP show higher incidences of thrush and allergic sensitivities 11 , 16 . In addition, IAP involves the possibility of maternal anaphylaxis 17 , and increasing rates of resistance to antibiotic agents necessitate alternatives to conventional IAP 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Newborns exposed to IAP show higher incidences of thrush and allergic sensitivities 11 , 16 . In addition, IAP involves the possibility of maternal anaphylaxis 17 , and increasing rates of resistance to antibiotic agents necessitate alternatives to conventional IAP 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated inappropriate or guideline discordant antibiotic use for penicillin allergic patients in the obstetrics population. 8,9 However, to our knowledge, our study is the first to evaluate appropriateness of antibiotics based on side-chain cross reactivity, and we found that most patients who received a non-β-lactam prophylaxis likely could have safely received cefazolin. Given the inferior outcomes and greater side-effect profile of non-β-lactam alternatives, 10 it is imperative that efforts be made to maximize β-lactam utilization in patients with a β-lactam allergy label.…”
Section: Discussionmentioning
confidence: 76%
“…In a previously published study, we examined 190 pregnant women who tested positive for group B streptococcus infection over a 3-year period who delivered at term who also had a self-reported penicillin or cefazolin allergy. 8 Women with low risk allergic-reaction (rash, itching or unknown reaction) represented 58% (99/171) of our penicillin-allergic group and would have been suitable candidates for confirmatory allergy testing. 8 Penicillin allergy testing during pregnancy is recommended for moderate risk groups too, inclusive of women reporting urticaria.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Women with low risk allergic-reaction (rash, itching or unknown reaction) represented 58% (99/171) of our penicillin-allergic group and would have been suitable candidates for confirmatory allergy testing. 8 Penicillin allergy testing during pregnancy is recommended for moderate risk groups too, inclusive of women reporting urticaria. 18 This suggests that up to 94% of women would have been eligible for penicillin allergy testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation